Association of thrombelastographic parameters with post-stenting ischemic events. (3rd June 2015) - Wang, Bo; Li, Xiao-Qing; Ma, Ning; Mo, Dapeng; Gao, Feng; Sun, Xuan; Xu, Xiaotong; Liu, Lian; Song, Ligang; Li, Xin-Gang; Zhao, Zhigang; Zhao, Xingquan; et al.
Abstract : Background and purpose: Thrombelastography (TEG) is widely used for the measurement of platelet function. However, few studies have investigated the TEG parameters in patients receiving extracranial or intracranial artery stenting for ischemic cerebrovascular disease. This study sought to describe the association of TEG parameters before the procedure with post-procedural ischemic events after extracranial or intracranial artery stenting. Methods: Patients in whom stenting was performed for extracranial or intracranial artery stenosis (70–99%) were recruited into the study. Blood samples were obtained for TEG to assess platelet function before stenting. The primary endpoint was ischemic stroke or transient ischemic attack in the territory of the stented artery. Results: A total of 218 patients were included in the study. During a mean follow-up period of 132 days (range 98–226 days), 18 (8.3%) primary endpoint events were recorded. Compared with patients without ischemic events, the ADP-induced platelet-fibrin clot strength (MAADP ) was significantly higher (41.57±15.10 vs 33.50±13.86, p=0.020) and the ADP inhibition rate (ADP%) was significantly lower in patients with ischemic events (39.54±23.15 vs 55.29±24.43, p=0.009). Multivariate analysis identified MAADP and ADP% as significant independent predictors of subsequent ischemic events with HRs of 1.036 and 0.965, respectively. From receiver operating characteristic curve analysis, MAADP >49.95 mm had the best predictive value of ischemic events. Conclusions: Our study suggests that TEG parameters MAADP and ADP% are associated with subsequent ischemic events in patients with extracranial or intracranial stents. Clinical trial number: NCT01925872.